Effect of Different Spacing Treatments on Yield from Anthocephalus chinensis Plantations - Singh, S. P.; Lal, Purushottam (Indian Forester, 1982)
The effect of different spacing treatments ou yield from Kadam plantations has been studied. Though the yield obtained from application of different spacings is not significantly different, it is observed that c1osest spacing of 1.83 m Ã— 1.83 m gives highest yield and the widest spacing of 3.66 m Ã— 3.66 m the lowest. The spacings appear to have direct effect on survival of plants. The survival percentage is maximum for widest spacing and minimum for closest spacings.